2019
DOI: 10.1093/humrep/dez184
|View full text |Cite
|
Sign up to set email alerts
|

Individualized ovarian stimulation in IVF/ICSI treatment: it is time to stop using high FSH doses in predicted low responders

Abstract: In IVF/ICSI treatment, the FSH starting dose is often increased in predicted low responders from the belief that it improves the chance of having a baby by maximizing the number of retrieved oocytes. This intervention has been evaluated in several randomized controlled trials, and despite a slight increase in the number of oocytes—on average one to two more oocytes in the high versus standard dose group—no beneficial impact on the probability of a live birth has been demonstrated (risk difference, −0.02; 95% C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 77 publications
(86 reference statements)
1
12
0
Order By: Relevance
“…Our review supports the recent ASRM recommendation that mild ovarian stimulation should be considered for IVF treatment in poor responders. Our conclusion also is in the line with a recent Cochrane review that found increasing or decreasing the stimulation dose according to ovarian reserve did not improve the pregnancy outcome over a fixed dose of 150 IU a day, while a dose less than 150 IU significantly reduced the incidence of OHSS ( Lensen et al , 2018 ); many researchers have demonstrated that increasing stimulation dose according to follicular reserve may yield more oocytes but that did not translate into an improvement in the pregnancy outcomes ( Arce et al , 2014 ; Leijdekkers et al , 2019 ). Overall, this updated review adds more data in favour of the mild approach, which could make IVF more patient-friendly, affordable and thereby more accessible worldwide.…”
Section: Discussionsupporting
confidence: 89%
“…Our review supports the recent ASRM recommendation that mild ovarian stimulation should be considered for IVF treatment in poor responders. Our conclusion also is in the line with a recent Cochrane review that found increasing or decreasing the stimulation dose according to ovarian reserve did not improve the pregnancy outcome over a fixed dose of 150 IU a day, while a dose less than 150 IU significantly reduced the incidence of OHSS ( Lensen et al , 2018 ); many researchers have demonstrated that increasing stimulation dose according to follicular reserve may yield more oocytes but that did not translate into an improvement in the pregnancy outcomes ( Arce et al , 2014 ; Leijdekkers et al , 2019 ). Overall, this updated review adds more data in favour of the mild approach, which could make IVF more patient-friendly, affordable and thereby more accessible worldwide.…”
Section: Discussionsupporting
confidence: 89%
“…Thus, development of future preparations of FSH may focus on matching the most active FSH forms with the least responsive of patients for which the originator or closely matched “biosimilars” may not optimally induce follicle growth and high-quality oocytes. This may ameliorate the conundrum of whether or not to increase the dose of FSH in patients that are low responders ( 94 ). Moreover, hypoglycosylated FSH which may have shorter half-life could afford greater control over hyperstimulation by virtue of faster clearance and easier dose control.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…For Japanese women with a low ovarian reserve and, therefore, at low risk of OHSS, 12 mg/d follitropin delta appeared to maximize the ovarian response and was associated with good pregnancy rates. It should be recognized that increasing the gonadotropin dose further in patients with a low ovarian reserve may not always overcome the risk of poor response or increase the chance of pregnancy and live birth (16). The main risk for women with either normal or high ovarian reserve is OHSS, and, therefore, a more granular approach in selecting the follitropin delta dose between the 6 mg/d to 12 mg/d range may be relevant to minimize the OHSS risk while maintaining a good probability for pregnancy.…”
Section: Figurementioning
confidence: 99%